Bisphosphonate treatment of bone disease. Issue 5 (25th April 2005) - Shaw, N J; Bishop, N J
Abstract : In 1997 a review article on bisphosphonates in this journal identified 24 published articles relating to children at that time. 1 Since then there has been a considerable increase in their use in clinical paediatric practice and research with there being nearly a further one hundred articles published at the time of writing.